Pengaruh Internet terhadap Interaksi Sosial pada Mahasiswa Universitas Sriwijaya - Sofita, Yunia Ruwanna; Sartika, Sartika; Audya, Meitiana; Ibrahim, Ali (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
This study aims to determine the effect of the internet on social interactions in students at Sriwijaya University. The thing that underlies the author doing the research is due to lack of direct communication between one student and another student. The influence of the internet has a major impact on the environment, especially in the campus environment, so many students who ignore a lot of things just because of the internet. In this case, many experts assess that communication is a very fundamental need for someone in a community life. Humans are social beings who still need other people in continuing their lives, the importance of direct communication should not be ignored by students today. Communication is a driver in interacting socially, in the absence of communication there can be no social life. Then it can be stated that social interaction is the foundation of all forms of social processes.